Optimization and dynamic characteristics of a new type of permanent magnet bias bearing. (November 2020) - Xiao, Ling; He, Xiwu; Cheng, Wenjie; Fan, Hongwei; Li, Ming
Unlike traditional magnetic thrust bearings, a new type of permanent magnet biased bearing structure made of soft magnetic composites in the bevel gear coupled rotor system was proposed that requires both lower eddy currents and greater thrust force. This paper presents the optimization of structure parameters, analysis of magnetic field and dynamic stiffness for two kinds of permanent magnet biased bearing. Firstly, the structural parameters for the bearing were optimized based on the adaptive particle swarm optimization. Secondly, the dynamic magnetic flux distribution for the permanent magnet biased bearing made of carbon steel at 1000 Hz was obtained by finite element method. Then, the equivalent reluctance models for the new type of permanent magnet biased bearing considering the effect of eddy currents are derived. Finally, based on the equivalent reluctance models, the dynamic force–current factor and force–displacement factor are given. The results show that the permanent magnet biased bearing made of soft magnetic composites can provide more stable electromagnetic force and larger bandwidth in the frequency range of 1000 Hz, and have greater electromagnetic force at the same frequency comparing with that made of carbon steel.